2010
DOI: 10.3989/scimar.2010.74n3455
|View full text |Cite
|
Sign up to set email alerts
|

Composition and distribution of subtidal and intertidal crustacean assemblages in soft-bottoms of the Ria de Vigo (NW Spain)

Abstract: SUMMARY:The intertidal and subtidal soft-bottoms of the inner area of the Ria de Vigo (NW Spain) were sampled in November and December 1999, and spatial distribution of crustacean species was examined. Environmental variables from water and sediment were measured at each sampling site. Amphipods and myocopids were the numerically dominant orders (49.9 and 26.9% dominance), amphipods accounting for more than 54% of identified taxa. The highest crustacean densities occurred with 55-41 species and 5953.6-4346.4 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Some other authors have demonstrated that modification in habitat complexity affects crustacean assemblages (Sanchez-Jerez et al 1999;Ayala and Martin 2003;Vazquez-Luis et al 2008). Indeed, the importance of temperature should be interpreted carefully, since Ysebaert and Herman (2002) pointed out that longterm averages of environmental variables are more important than values obtained during samplings (Cacabelos et al 2010). Nevertheless, the difference in mean density between months can be explained by the ecological preferences of each species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some other authors have demonstrated that modification in habitat complexity affects crustacean assemblages (Sanchez-Jerez et al 1999;Ayala and Martin 2003;Vazquez-Luis et al 2008). Indeed, the importance of temperature should be interpreted carefully, since Ysebaert and Herman (2002) pointed out that longterm averages of environmental variables are more important than values obtained during samplings (Cacabelos et al 2010). Nevertheless, the difference in mean density between months can be explained by the ecological preferences of each species.…”
Section: Discussionmentioning
confidence: 97%
“…Variations in temperature and salinity have been cited by a number of authors as important factors for the occurrence of particular amphipod species (Nevis et al 2009;Mogias and Kevrekidis 2005). In fact, many ecological studies have shown salinity to be the main factor controlling zonation in the structure of the benthic communities (Cacabelos et al 2010). However, Bazairi et al (2003) have emphasized that this is not the main factor in brackish environments.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in the Atlantic zone of the Iberian Peninsula found between 34 and 79 different amphipod species in the northwestern area (Cunha et al 1999, Lourido et al 2008, Cacabelos et al 2010 and 93 species on the southern Portuguese coast (Carvalho et al 2012). On the other hand, in the Mediterranean area, an inventory of soft-bottom amphipods from the east coast of the Iberian Peninsula revealed the presence of 55 different species (de-la-Ossa-Carretero et al 2010).…”
Section: Biogeographical Considerationsmentioning
confidence: 99%
“…This species is recorded from all over the world, including Australia (Edgar 2008), Bermuda (Greve 1974), California (Richardson 1905, Sieg 1980, Japan (Shiino 1951), Sri Lanka (Stebbing 1905) and Spain (Cacabelos et al 2010). Such a cosmopolitan distribution is highly unlikely for organisms with low dispersal potential, such as tanaids (Larsen 2005), so the presence of a species complex is expected.…”
Section: Introductionmentioning
confidence: 99%